Music fandom in the digital age - Baym, Nancy; Cavicchi, Daniel; Coates, Norma (The Routledge Companion to Media Fandom, 2017)
The field of fan studies has seen exponential growth in recent years and this companion brings together an internationally and interdisciplinarily diverse group of established scholars to reflect on the state of the field and to point to new research directions. Engaging an impressive array of media texts and formats and incorporating a variety of methodologies, this collection is organized into six main sections: methods and ethics, technologies and practices, identities, race and transcultural fandom, industry, and futures. Each section concludes with a conversation among some of the field’s leading scholars and industry insiders to address a wealth of questions relevant to each section topic.